2020
DOI: 10.1021/acsomega.9b04483
|View full text |Cite
|
Sign up to set email alerts
|

Role for Metallothionein-3 in the Resistance of Human U87 Glioblastoma Cells to Temozolomide

Abstract: Metallothioneins (MTs) are metal-binding proteins that are overexpressed in various human cancers and are thought to be associated with resistance to cytotoxic drugs. The knowledge on MT expression, regulation, and function in human gliomas is limited. We found that MT3 mRNA was highly expressed in cell lines derived from grade IV gliomas ( i.e ., A172 and U87 cells), as compared to grade II astrocytoma cells ( i.e ., 1321N1). Different from 1321N1, U87 cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Glioblastoma cells were treated with the highest DOX concentration—15 µM ( Figure 4 ). The resistance of U87 cells considered as sensitive in our model is probably due to the deregulation of the cell cycle and the absence of apoptosis [ 24 ]. The death of tested sensitive cells (NCI-H460, DLD1 and U87) occurred after 80, 85 and 15 min (respectively) of drug injection ( Figure 2 , Figure 3 and Figure 4 ), and the corresponding drops in variance were statistically significant ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Glioblastoma cells were treated with the highest DOX concentration—15 µM ( Figure 4 ). The resistance of U87 cells considered as sensitive in our model is probably due to the deregulation of the cell cycle and the absence of apoptosis [ 24 ]. The death of tested sensitive cells (NCI-H460, DLD1 and U87) occurred after 80, 85 and 15 min (respectively) of drug injection ( Figure 2 , Figure 3 and Figure 4 ), and the corresponding drops in variance were statistically significant ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lonafarnib (LNF; Sigma Aldrich) and Temozolomide (TMZ; Sigma Aldrich) were reconstituted in DMSO according to the manufacturer's protocol and were diluted in culture media for treatment. At Day 7, GBM:astrocytes, GBM:EC, and triculture MCTS were treated with 5 μM LNF, 100 μM TMZ or their combination (5 μM LNF + 100 μM TMZ) for 48 h. These concentrations were chosen based on previous studies that have demonstrated that TMZ (100 μM) targeted MGMT and telomerase activity, and LNF (5 μM) inhibited the neurosphere formation in GBM cells 25,27–34 …”
Section: Methodsmentioning
confidence: 99%
“…At Day 7, GBM:astrocytes, GBM:EC, and triculture MCTS were treated with 5 μM LNF, 100 μM TMZ or their combination (5 μM LNF + 100 μM TMZ) for 48 h. These concentrations were chosen based on previous studies that have demonstrated that TMZ (100 μM) targeted MGMT and telomerase activity, and LNF (5 μM) inhibited the neurosphere formation in GBM cells. 25,[27][28][29][30][31][32][33][34] 2.4 | Optical microscopy and image analysis 3D MCTS were monitored using an Olympus IX83 microscope with a spinning disc confocal attachment. The size and the cross-sectional area of the spheroids were analyzed using ImageJ software (NIH) as described previously.…”
Section: Drug Treatmentmentioning
confidence: 99%
“…To obtain TMZ (Sigma, 76899, USA) resistant cell lines, we gradually increased the exposure of U87 cells from 5 to 100 μmol/l of TMZ. The TMZ-resistant U87 cells were named U87/R cells 29 .…”
Section: Methodsmentioning
confidence: 99%